Green Synthesis Nanopartikel Perak Menggunakan Ekstrak Daun Bayam Duri (Amaranthus spinosus L.) dan Aktivitasnya Sebagai Antibakteri - Setya Restu Pambudi; Ismi Rahmawati; Teuku Nanda Saiffulah Sulaiman (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2024)
Spinach leaves contain flavonoids and phenolic compounds. The hydroxyl groups in phenolic compounds can be used in the synthesis of silver nanoparticles. The aim of this research is to determine the optimal time and pH for reducing silver ions (Ag+) into silver nanoparticles (Ag0) with ethanol extract of spinach leaves as bioreductor seen from the maximum wavelength response and absorbance value using the Central Composite Design method, characteristics of the synthesis results and activity antibacterial Escherichia coli and Staphylococcus aureus bacteria. Extraction using maceration method in 80% ethanol. Optimization of synthesis using Central Composite Design resulted in 13 experiments with time reaction and pH as dependent variables, Surface Plasmone Resonance (SPR) response wavelength and absorbance as independent variables. Formation of silver nanoparticles can be seen from the SPR. Characterization of nanoparticles at particle size, distribution, stability, surface morphology and particle composition. Observation of antibacterial activity was using a diffusion method. Result screened phytochemicals spinach extract contains flavonoids, phenolics, tannins, and saponins. The ethanol extract spinach leaves can reduce AgNO3 into silver nanoparticles at concentration of 1 mM AgNO3 with ratio of 3 mL extract and 30 mL AgNO3, temperature 70oC, time 60 minutes, and pH 9.05. The colloidal particle size of AgNPs is 90.4 ± 1.2 nm, the zeta potential -35.633 ± 0.478 mV. The particle morphology of AgNPs was non homogeneous with an average particle size 136 nm. The chemical composition shows that the silver (Ag) element dominates with a weight concentration of 67.868% and an atomic concentration of 49.685% of the spectrum peak at 3 KeV. AgNPs have the ability to inhibit Staphylococcus aureus as shown by the inhibitory zone diameter of 11 mm and Escherichia coli of 9.7 mm.